(untitled) (Campo Abierto. Revista de Educación y Psicología, 2016)
Part of a more ambitious, ongoing study on the socio-health state of de popultion of the city of Badajoz. The present papar concentrates on alcohol and tobacco consumption for being two socially accepted drugs wich gererate multiple problems and avoidable through an adequate education on the sub jet.